Synergy of fun walk and culinary tourism in UNPAD tourism fest 2024: sustainable tourism perspective - Delamontano, Eldo; Lumongga, Az Zahra; Annisa, Sekar Dinda; Novianti, Evi; Endyana, Cipta; Winoto, Yunus (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
This study investigates the strategic role of fun walking as a recreational sport in enhancing tourism events and its direct contribution to culinary bazaar visitation. While traditionally perceived as recreational and a healthy lifestyle, fun walks were integrated into the Unpad Tourism Festival 2024 to support its culinary bazaar activities, offering a novel approach to event management. The research employed a mixed-methods approach, combining observations and literature studies with a survey of 47 fun walk participants, data were analyzed using descriptive statistic. Findings from this investigation reveal that fun walk participants significantly contributed to both the increase in visitor numbers and extended visit duration at the culinary bazaar. Furthermore, the innovative packaging of fun walk activities, particularly through the incorporation of tour guides, significantly enhanced the quality of the participant experience, leading to a measurable increase in overall event visitor satisfaction. This study confirms that an interactive experience, seamlessly blending sports, entertainment, and targeted tourism promotion, provides actionable insights for committee. The results underscore the critical importance of integrating recreational sports activities with the broader objective of promoting cultural, culinary, and urban tourism attractions, offering a powerful model for enhancing event success and visitor engagement in future tourism initiatives.